1997
DOI: 10.1002/clc.4960201207
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of intravascular ultrasound studies: Predictors of imaging success before coronary interventions

Abstract: SummaryBackground: Intravascular ultrasound (IVUS) is currently used to study lesions during transcatheter coronary therapy. However, before dilation some lesions cannot be reached or crossed with the imaging catheter.Hypothesis: This study seeks to elucidate which factors determine the feasibility of IVUS examination before coronary interventions.Methods: Accordingly, 100 consecutive patients undergoing IVUS examination before coronary angioplasty were prospectively studied. The clinical and angiographic char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…In the current study, predictors of failure of TA were generally lesionspecific rather than patient-dependent. Previously, the presence of marked tortuosity and coronary calcification have been identified to be predictors of failure of intravascular ultrasound imaging, at a rate of 23% failed procedures described in a prospective cohort of patients with stable or unstable angina (16). The difference in flexibility of the catheters used for intravascular ultrasound with those currently used for TA and the dissimilar patient characteristics may explain the lower failure rate we observed.…”
Section: Discussioncontrasting
confidence: 47%
“…In the current study, predictors of failure of TA were generally lesionspecific rather than patient-dependent. Previously, the presence of marked tortuosity and coronary calcification have been identified to be predictors of failure of intravascular ultrasound imaging, at a rate of 23% failed procedures described in a prospective cohort of patients with stable or unstable angina (16). The difference in flexibility of the catheters used for intravascular ultrasound with those currently used for TA and the dissimilar patient characteristics may explain the lower failure rate we observed.…”
Section: Discussioncontrasting
confidence: 47%
“…Although the guidewire tends to straighten the proximal curves of instrumentalized vessels, the distal advancement of these catheters and their capability to negotiate tortuous vessels remains restricted. In a previous study [11], we found that catheter size, baseline minimal lumen diameter, proximal tortuosities, and lesion calcification were independent predictors of failure to cross the target lesion. If too much force is inadvertently applied to advance the IVUS catheter, displacement of the catheter, away from the guidewire, could be induced [11], and then the guidewire may be kinked and caught within the imaging system.…”
Section: Discussionmentioning
confidence: 67%
“…Nowadays, IVUS imaging is a user-friendly technique widely used during coronary interventions [1,2]. In our experience [11], the presence of tortuous proximal coronary segments hampers catheter manipulation and advancement across the target lesion. Although the guidewire tends to straighten the proximal curves of instrumentalized vessels, the distal advancement of these catheters and their capability to negotiate tortuous vessels remains restricted.…”
Section: Discussionmentioning
confidence: 91%
“…However, there is a growing interest in applying intracoronary ultrasound (ICUS) as an additional imaging tool since quantitative coronary ultrasound (QCU) allows the evaluation of not only the lumen (QCA) but also the vessel wall [9][10][11][12][13][14][15][16]. This is of particular interest in restenosis or progression-regression studies [17].…”
Section: Introductionmentioning
confidence: 99%